Formononetin: A Pathway to Protect Neurons - Ma, Xiaoyu; Wang, Juejin (Frontiers in Integrative Neuroscience, 2022)
Formononetin (FMN) is a phytoestrogen member of the flavonoid family, which has the pharmacological effects of antioxidative, antihypertensive, antitumor, and anti-infective. FMN demonstrates potential in the prevention and treatment of diseases, specifically neurological diseases, such as traumatic brain injury (TBI), spinal cord injury (SCI), ischemic stroke, cerebral ischemia-reperfusion, Alzheimer’s disease, and nerve tumor. Herein, a literature search is conducted to provide information on the signaling pathways of neuroprotection of formononetin based on the neuroprotective study. The significant neuroprotective function of FMN makes it a novel candidate for the development of drugs targeting the central nervous system.